THE IMPACT OF SELECTED SOCIO ECONOMIC FACTORS ON DEFENSE EXPENDITURES IN SOUTHEASTERN EUROPEAN COUNTRIES : DOI: 10.5937/etp2402001S - Šare, Dalibor (Ekonomija - teorija i praksa, 2024)
This research explores the influence of certain socio- economic factors on defense expenditures in Southeastern European countries. The research was conducted for the period from 2005 to 2021. The aim of the research is to examine the impact of political stability, budgetary allocations for education, and revenues from taxes on goods and services, as independent variables, on defense expenditures as a dependent variable using the STATA software package. By applying the chosen model, the extent to which variations in defense expenditures can be explained by the independent variables used in the model was determined. The conclusion of the research is that the variables used in the model have a significant impact on defense expenditures and provide insight into the complex interactions between social and economic factors and defense expenditures in Southeastern European countries.